2014
DOI: 10.5539/jas.v6n10p188
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Antinutritional Factors in Whole Leaves of Enterolobium cyclocarpum by Aspergillus niger Using Solid State Fermentation

Abstract: In the tropics, native pastures and crop residues constitute the major feed resources for ruminants. There are available seasonally and of low quality. They contribute to the limitation of ruminant production which is predominantly managed by small holders. Enterolobium cyclocarpum (EC) is a hardy multipurpose tree (MPT) that has potential as supplement for ruminant feeding. However, anti nutritional factors (ANFs) contained in the leaves of EC could have negative effects on its nutritive value. Fungal biodegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…J. curcas seeds(Oseni and Akindahunsi, 2011) and E. cyclocarpum leaf meal(Ayuk et al 2014) could corroborate the present result. The increased total avonoid content (by 31.77%) in the present study could be due to the complete breakdown of the plant cell wall matrix by the extracellular enzymes (cellulase, xylanase and pectinase) produced by the A. niger during fermentation.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…J. curcas seeds(Oseni and Akindahunsi, 2011) and E. cyclocarpum leaf meal(Ayuk et al 2014) could corroborate the present result. The increased total avonoid content (by 31.77%) in the present study could be due to the complete breakdown of the plant cell wall matrix by the extracellular enzymes (cellulase, xylanase and pectinase) produced by the A. niger during fermentation.…”
supporting
confidence: 90%
“…After the fermentation of MOLM, its crude protein and total lipid level have increased; however, the crude bre level has decreased. The rise in crude protein level in FMOLM might be associated with the contribution of microbial protein(Ayuk et al 2014) or from the breakdown of the protein-antinutrient complex by the microbial enzymes(Amankwah et al 2009). In support of the present study,Zhang et al (2020) reported the increased protein content in A. niger fermented M. oleifera leaves after 7 days of fermentation.…”
supporting
confidence: 86%
“…African yam bean (Sphenostylis stenocarpa) is an underutilized grain legume known in homesteads of Central and West Africa (Adeparusi 2001). Cocoa pod husk is a fibrous by -product of cocoa (Theobroma cacao) processing when the edible been has been removed (Ayuk et al 2007). Digestibility estimation is essential in assessing the nutritive value of feed as well as other nutritious residues and notable for adequate balancing of diets (Detmann et al, 2007).…”
Section: LXXIImentioning
confidence: 99%
“…The leaves were previously inoculated with A. niger and incubated at 30˚C for five periods (0, 7, 14, 21 and 28 days). A. niger was originally isolated at the Department of Yam pathology, International Institute of Tropical Agriculture and maintained on potato dextrose agar (PDA) slants [21]. After each incubation period, samples were oven dried at 60˚C, allowed to cool and ground for mineral analysis and in sacco dry matter degradability.…”
Section: Location and Foragementioning
confidence: 99%